Les Real Life Super Heroes - Éric Maigret (Communication)
In recent years, fans of superheroes have appeared in the streets of American cities dressed in their distinctive disguise. To understand this, the author has conducted personal interviews and done case studies of websites and forums on the Internet. He concludes that these public “appearances” cannot be understood as mimetic behaviour but rather as a mediated integration into the “celebrity culture” typical of what Ulrich Beck calls the new or reflexive modernity.